Curcuma Longa (Turmeric) Bioactive Extraction Using High Pressure Processing (HPP) For Enhanced Quality Content and Nutraceutical Properties - IRFAN NURHARRIZ BIN MOHD USRI; Angzzas Sari Binti mohd Kassim (Progress in Engineering Application and Technology, 2025)
A study examined the extraction of bioactive compounds from turmeric (Curcuma Longa) using High-Pressure Processing (HPP) as an alternative to conventional methods, which often rely on chemical solvents and can degrade valuable compounds. The research tested different pressure levels (200, 400, and 600 MPa), extraction times (4, 6, and 10 minutes), and solid-to-liquid ratios (1:5, 1:10, and 1:15). The optimal results were achieved at 400 MPa, with a 6-minute extraction time and a 1:10 ratio, yielding the highest concentration of bioactive compounds at 0.42 mg/mL. Lower pressures required longer extraction times, while higher pressures caused some degradation of the compounds. The extracts demonstrated significant anti-inflammatory, antioxidant, and antimicrobial properties, highlighting the potential of HPP for producing natural health supplements and functional foods. Future research should focus on scaling up this method and exploring its combination with other advanced extraction techniques for improved efficiency and stability.